Bringing the individual into the co-creation of value. Issue 7 (12th December 2019) - Ranjan, Kumar Rakesh; Read, Stuart
Abstract : Purpose: Despite the increasing prominence of value co-creation (VCC) in extant research, the area of customer co-creation is in its infancy and many aspects are not well-understood. This paper aims to important work from the individual psychology literature with the concept of VCC and offers empirical evidence to untested theoretical claims regarding the role of the individual in VCC. Design/methodology/approach: The investigation begins with reviews of the literature of individual psychology and VCC to compare the concepts they use to explain the role of the individual in co-creation. The results of the theoretical development are empirically derived using a multiple vignette-based study to examine relationships between individual characteristics and the activity of VCC. Findings: The authors find a positive effect of a customer's prosocial orientation, perspective taking and involvement on VCC. However, a customer's extraversion does not affect the degree of VCC. The desire-to-participate mediates these relationships. Research limitations/implications: This study offers a foundation for some of the central claims about VCC and encourages a precise understanding of the impact of individual customer psychology in value co-creation with firms. Implications for the service-dominant logic of marketing and core work in psychology are discussed. Practical implications: Managers seeking to design co-creative ecosystems need to know about the individuals they are co-creating with. In this research, the authors clearly exemplify how managers can use in practice a theoretical understanding of individuals to better direct the activity of VCC. Originality/value: This paper provides both new theoretical knowledge from the parallel literature review and exciting empirical results from the authors' investigation into phenomenological claims regarding VCC.